Laser dressing effects on the energy spectra in different shaped quantum wells under an applied electric field - Radu, A; Niculescu, E; Cristea, M (Journal of Optoelectronics and Advanced Materials, 2008)
The influence of a laser field on the subband energy levels in finite V-shaped, parabolic and square GaAs-GaAlAs quantum wells under the electric field is studied by using a variational method in the effective mass approximation. The dependence of the interband optical absorption on the laser field amplitude, the geometric shape of the quantum wells, and the applied electric field is discussed.